1989
DOI: 10.1007/bf02425970
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade percutaneous dilation of ureteral strictures after kidney transplantation

Abstract: Ureteral obstruction after renal transplantation is due mostly to retroperitoneal fibrosis in the area of surgical dissection, and pyeloureterostomy is the treatment of choice for such an obstruction. For confined strictures, especially at the site of the ureteroneocystostomy, endoscopic dilation may be a good alternative. Antegrade percutaneous dilation was used to treat six patients with ureteral stricture after kidney transplantation. Four patients had stricture at the ureterovesical junction, one a confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Peregrin et al reported successful dilation in 96 YO of 23 patients, but long-term success in only 50% [9]. Similar results have been reported by others [5, 8,10,111. The main disadvantage of this method is the uncontrolled destruction of ureteral and periureteral tissue by the dilation.…”
Section: Discussionsupporting
confidence: 66%
“…Peregrin et al reported successful dilation in 96 YO of 23 patients, but long-term success in only 50% [9]. Similar results have been reported by others [5, 8,10,111. The main disadvantage of this method is the uncontrolled destruction of ureteral and periureteral tissue by the dilation.…”
Section: Discussionsupporting
confidence: 66%
“…In the first line percutaneous or endoscopic dilation is recommended, success rates are up to 85 YO [2,11,14,19,23,31].…”
Section: Resultsmentioning
confidence: 99%
“…In cases of confined ureteral obstruction, especially stricture of the ureter-bladder anastomosis, a percutaneous antegrade di lation or incision of the strictured area may be done. Our limited experience with 6 patients was good in 4, with now a mean follow-up of 24 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of both conditions is mainly surgical [2,13]. In selected cases of confined ureteral stricture a percutaneous endourologic treatment is also possible [4,6,11].…”
mentioning
confidence: 99%